Análise diagnóstica da informática na educação nos 4º e 5º anos do ensino fundamental I em Foz do Iguaçu/PR - Segantini, Jésus Henrique (2017)
The insertion of Informatics in Education has brought about changes in several aspects in the schools, mainly in the communication, relationship, and, specially, in the teaching methodologies. Actions of public policies have promoted and guided the inclusion of Information and Communication Technologies (ICT) in the educational context in the last decades, but the reality found in the schools is still not the one expected. Devices such as applications, educational websites and social networks have been more and more used as pedagogical support and as collaborative virtual spaces. This Master's research has as its central goal to diagnose and analyze the teaching practices with the use of ICT in the computer labs, through the perception of the teachers from 4th and 5th years of Elementary School in the city of Foz do Iguaçu/PR, and the actions of continuous training by the Municipal Educational Technology Center (NTM). The individuals who took part in this research were the laboratory teachers, regent teachers, school managers, NTM's manager and the pedagogical coordinator of Educational Computing of the Municipal Education Secretariat (SMED). The research had descriptive exploratory character with qualitative and quantitative analysis. The methodological process used questionnaires as research tools with questions about the practices developed with the use of ICT, the integration between the laboratory teacher and the regent teachers, the infrastructure of the laboratories and also the provision of continuous training for the use of ICT. The results showed that schools in the city of Foz do Iguaçu face obstacles in the structures of their computer labs with deprecated and outdated machines, lack of quality access to the Internet, which often limits the developed activities, as well as the lack of integration between the laboratory teacher and the regent one in the preparation of laboratory activities. Regarding continued training, although offered, the participants reported the need to change the methodology of some offered courses, such as schedules and topics related to the planning and insertion of ICT as pedagogical resources. With the data obtained, it was possible to diagnose the reality of the educational environments in Foz do Iguaçu regarding the use of the technologies and with that initiate possible discussions that can contribute to new actions for teaching and learning processes mediated by the ICT.